Psychological status of healthcare workers in the post-COVID 19 period in China: a retrospective multicentric cross-sectional study - Wang, Xiaoli; Fu, Fang; Gan, Aihua; Wu, Yuqian; Pan, Wenjing; Zhou, Xin; Zhang, Xiaohui (Frontiers in Psychiatry, 2025)
ObjectiveThis study aimed to assess the depression, anxiety, sleep disorders, and post-traumatic stress disorder (PTSD) among healthcare workers (HCWs) in Huizhou in the post-pandemic period.MethodsA retrospective multicentric cross-sectional study was conducted from April 25 to May 25, 2023, involving 4,618 HCWs from 46 hospitals in Guangdong Province, China. Psychological well-being was measured using the PHQ-9, GAD-7, Insomnia Severity Index (ISI), and PTSD scales. Chi-square test and multivariable logistic regression were used to identify factors associated with depression, anxiety, insomnia and PTSD.ResultsThe rates of anxiety, depression, insomnia, and PTSD were 45.0%, 59.4%, 40.5%, and 10.5%, respectively. HCWs who did not experience negative events were more likely to show anxiety (OR=2.082, 95%CI:1.734-2.499), depression (OR=2.013, 95%CI:1.647-2.460) and insomnia (OR=2.013, 95%CI:1.683-2.409).ConclusionThere was a high prevalence of anxiety, depression, insomnia, and PTSD in the HCWs after the COVID-19 pandemic.